A phosphorus-free and slag-free alkali film forming agent for high carbon steel drawing and its preparation method and application

CN122941483APending Publication Date: 2026-10-20YINGXING NEW MATERIALS (GUANGDONG) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611229221.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-13
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

(1)彻底解决吸潮与拉丝粉结焦:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention discloses a phosphorus-free, slag-free, moisture-resistant alkaline film-forming agent for high-carbon steel drawing, its preparation method, and its application, belonging to the technical field of film-forming agents. The alkaline film-forming agent of this invention comprises the following components by mass percentage: 5%~15% modified fatty acid soap; 1%~5% soluble calcium salt; 1%~5% hydrophobically modified nano-silica; 2%~8% amino silicone oil emulsion; 1%~5% gluconate; 0.5%~2% tartrate; 1%~3% triethanolamine; and the balance being deionized water. The modified fatty acid soap includes stearate and isostearate, with a mass ratio of stearate to isostearate of 3:1~5:1. The alkaline film-forming agent of this invention exhibits good stability, no sedimentation, is environmentally friendly, low in cost, and has a simple preparation process. It forms a uniform and dense film with good adhesion and is moisture-free. When used for high-carbon steel drawing, it prevents coking, die breakage, and wire skipping, reduces die wear, and improves the quality and efficiency of high-carbon steel drawing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coating agent technology, specifically relating to a phosphorus-free, slag-free, moisture-resistant alkaline coating agent for high-carbon steel drawing, its preparation method, and its application. Background Technology

[0002] High-carbon steel requires surface coating treatment before drawing to accommodate the drawing powder. Traditional phosphating solutions contain phosphorus and heavy metals, and produce a large amount of slag. While commercially available alkaline physical coating agents are environmentally friendly and slag-free, they suffer from a fatal flaw: their coatings have a porous microcrystalline structure and are highly hydrophilic. In summer or high-temperature, high-humidity environments, the wire easily absorbs moisture after exiting the drawing bath. During drawing, the moisture on the coating surface, under high temperature and pressure, causes the drawing powder (such as soap powder) to hydrolyze, soften, or even carbonize, forming hard coke on the drawing die surface. This not only leads to a dramatic increase in die consumption and frequent die breakage but also causes the wire to skip or break on the rollers. Furthermore, once the die is coked, it is extremely difficult to clean, requiring tools to pry it open, severely restricting production efficiency and product quality. Additionally, the acid introduced during the wire pretreatment pickling process easily reacts with the alkaline physical coating agent to form sediment, disrupting the bath balance.

[0003] Therefore, developing a coating agent that is slag-free in alkaline environments, acid-resistant, and can completely solve the problems of high humidity absorption and prevent coking of wire drawing powder is an urgent problem to be solved in this field. Summary of the Invention

[0004] To overcome the shortcomings of the prior art, this invention provides a phosphorus-free, slag-free, moisture-resistant alkaline film agent for high-carbon steel drawing, its preparation method, and its application; the alkaline film agent of this invention is slag-free in alkaline environments, acid-resistant, and can completely solve the problem of high humidity absorption and prevent coking of drawing powder.

[0005] The technical solution adopted by this invention to solve its technical problem is: This invention provides a phosphorus-free, slag-free, moisture-absorbing, alkaline film-forming agent for drawing high-carbon steel, comprising the following components by weight percentage: Modified fatty acid soap 5%~15%; Soluble calcium salts 1%~5%; 1%~5% hydrophobically modified nano-silica; Amino silicone oil emulsion 2%~8%; Gluconate 1%~5%; Tartrates 0.5%~2%; Triethanolamine 1%~3%; Deionized water balance; Modified fatty acid soaps include stearate and isostearate, with a mass ratio of stearate to isostearate of 3:1 to 5:1.

[0006] Preferably, the stearate is potassium stearate and / or sodium stearate.

[0007] Preferably, the isostearate is potassium isostearate and / or sodium isostearate.

[0008] Preferably, the soluble calcium salt is one or more of calcium gluconate, calcium chloride, and calcium nitrate.

[0009] Preferably, the mass ratio of gluconate to calcium ions in the alkaline film-forming agent is 5:1 to 20:1.

[0010] More preferably, the mass ratio of gluconate to calcium ions in the alkaline film-forming agent is 12:1 to 20:1.

[0011] Preferably, the hydrophobically modified nano-silica is fumed silica with a surface modified by long-chain alkylsilanes and a water contact angle ≥110°.

[0012] Preferably, the amino silicone oil emulsion is a terminal amino or side amino polyether modified silicone oil emulsion with a solid content of 20% to 40%.

[0013] Preferably, the gluconate is sodium gluconate and / or potassium gluconate.

[0014] Preferably, the tartrate is potassium sodium tartrate.

[0015] Preferably, the pH of the alkaline film-forming agent is 9.0~10.5.

[0016] This invention provides a method for preparing the above-mentioned phosphorus-free, slag-free, moisture-absorbing alkaline film agent for drawing high-carbon steel, comprising the following steps: Under stirring conditions, modified fatty acid soap and triethanolamine are added to heated deionized water, followed by gluconate and tartrate, then hydrophobically modified nano-silica and amino silicone oil emulsion, and finally soluble calcium salt. After cooling, the pH is adjusted to obtain a phosphorus-free, slag-free, moisture-absorbing alkaline coating agent for high carbon steel drawing.

[0017] Preferably, the temperature of the heated deionized water is 50~60℃.

[0018] Preferably, after adding the modified fatty acid soap and triethanolamine, the mixture is stirred until completely dissolved.

[0019] Preferably, after adding gluconate and tartrate, the mixture is stirred until completely dissolved.

[0020] Preferably, after adding the hydrophobically modified nano-silica and amino silicone oil emulsion, stir for 30-45 minutes.

[0021] Preferably, the hydrophobically modified nano-silica and amino silicone oil emulsion are premixed evenly.

[0022] Preferably, after adding the soluble calcium salt, stir for 15-30 minutes.

[0023] Preferably, the soluble calcium salt is pre-dissolved in deionized water at a mass concentration of 30-50%.

[0024] Preferably, the pH is adjusted to 9.0~10.5.

[0025] Preferably, the mixture is cooled to room temperature.

[0026] Preferably, the pH is adjusted and then filtered through a 200-400 mesh filter.

[0027] This invention provides the application of the above-mentioned phosphorus-free, slag-free, moisture-absorbing, alkaline film-forming agent for high-carbon steel drawing in the high-carbon steel drawing process.

[0028] This invention provides a method for drawing high-carbon steel, comprising the following steps: High-carbon steel is immersed or sprayed with the above-mentioned alkaline coating agent, drained or dried, then coated with wire drawing powder and then drawn into shape.

[0029] Preferably, the high-carbon steel is pre-degreased, derusted, and washed with water until neutral.

[0030] Preferably, high-carbon steel is used for wire rod.

[0031] Preferably, the immersion time of high carbon steel in the alkaline coating agent is 240-300 seconds.

[0032] Preferably, the drying temperature is 70~80℃ and the time is 240~300 seconds.

[0033] The advantages of this invention are as follows: (1) Completely solve the problems of moisture absorption and coking of drawing powder: Hydrophobic modified nano-silica cuts capillaries, and amino silicone oil constructs a flexible low surface energy network, resulting in a film contact angle >105°. It does not whiten or absorb water after 24 hours in a high humidity environment of 40℃ / 90%RH, and the die surface remains dry during drawing, completely eliminating coking, die breakage, and wire skipping, extending die life by more than 30%.

[0034] (2) The bath solution is extremely stable and completely free of residue: The strong complexing and crystal-controlling effect of sodium gluconate and potassium sodium tartrate stabilizes and chelates free calcium ions, inhibiting the formation of macroscopic precipitates. No bottom sediment is observed after three months of continuous use of the solution, eliminating the need for frequent tank cleaning and reducing the wastewater treatment load.

[0035] (3) Strong process compatibility, environmentally friendly and efficient: The entire system is alkaline (pH 9.0~10.5), completely free of phosphorus, fluorine, and heavy metals, and wastewater can be directly neutralized and precipitated before discharge. It forms films quickly and can be dried at room temperature or low temperature, making it suitable for high-speed continuous fiber drawing production lines.

[0036] (4) The raw materials are inexpensive and readily available, and the preparation is simple: It replaces expensive specialty polymers with conventional fatty acid potassium salts, sodium gluconate, silicone oil, etc., and can be prepared by stirring at room temperature without the need for high-speed grinding or complex emulsification equipment, resulting in extremely low industrialization costs.

[0037] The beneficial effects of this invention are: The phosphorus-free, slag-free, moisture-resistant alkaline film-forming agent for high-carbon steel drawing of the present invention has good stability, no sediment, is environmentally friendly, low cost, and simple preparation process. It forms a uniform and dense film with good adhesion and does not absorb moisture. When used for high-carbon steel drawing, it does not cause coking, die breakage, or wire skipping, reduces die wear, and improves the quality and efficiency of high-carbon steel drawing processing. Attached Figure Description

[0038] Figure 1 Electron micrographs of high-carbon steel specimens after being impregnated with an alkaline coating agent and dried, as shown in Example 2 and Comparative Example 5 of the present invention. Detailed Implementation

[0039] The present invention will be further described below with reference to embodiments.

[0040] The following will clearly and completely describe the concept, specific solutions, and technical effects of the present invention with reference to embodiments, so as to fully understand the purpose, features, and effects of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention. The various technical features in the present invention can be combined interactively without contradicting each other.

[0041] This invention provides a phosphorus-free, slag-free, moisture-absorbing, alkaline film-forming agent for drawing high-carbon steel, comprising the following components by weight percentage: Modified fatty acid soap 5%~15%; Soluble calcium salts 1%~5%; 1%~5% hydrophobically modified nano-silica; Amino silicone oil emulsion 2%~8%; Sodium gluconate 1%~5%; Potassium sodium tartrate 0.5%~2%; Triethanolamine 1%~3%; Deionized water balance.

[0042] The modified fatty acid soap is a mixture of potassium stearate and potassium isostearate (mass ratio 3:1 to 5:1), which breaks the regular crystallization of traditional calcium soap and makes the film layer dense. The soluble calcium salt is calcium gluconate, calcium chloride, or calcium nitrate, providing film-forming calcium ions; The hydrophobically modified nano-silica is fumed silica with a water contact angle ≥110° after surface modification with long-chain alkylsilanes; the amino silicone oil emulsion is a silicone oil emulsion modified with terminal amino or side amino polyethers, with a solid content of 20%~40%. Sodium gluconate and potassium sodium tartrate act as complexing and crystal-controlling agents to stabilize the bath solution and refine the crystals.

[0043] This invention provides a method for preparing the above-mentioned alkaline film-forming agent, comprising the following steps: (1) Heat the deionized water to 50~60℃, maintain the temperature, and add the ingredients sequentially under stirring conditions; (2) Add the modified fatty acid soap and triethanolamine in sequence, and stir until completely dissolved / transparent to obtain soap solution A; (3) Add sodium gluconate and potassium sodium tartrate to soap solution A, stir to dissolve, and obtain complex solution B; (4) The hydrophobic modified nano silica and amino silicone oil emulsion are premixed and dispersed evenly, and then slowly added to complexing solution B. Stirring is continued for 30-45 minutes to obtain mixture C; (5) Dissolve the soluble calcium salt in a small amount of deionized water, then slowly add it dropwise to the mixture C, react and stir evenly, cool to room temperature, finely adjust the pH to 9.0~10.5 with acid / base, filter and package.

[0044] This invention provides the application of the above-mentioned alkaline film-forming agent in the drawing of high-carbon steel, comprising the following steps: After pretreatment to remove oil and rust and washing with water until neutral, the high-carbon steel wire is immersed in the alkaline coating agent for 240-300 seconds or sprayed with the alkaline coating agent. It is then taken out and drained or dried with hot air at 70-80℃, and then uniformly coated with wire drawing powder for drawing and shaping.

[0045] The working mechanism of the phosphorus-free, slag-free, moisture-absorbing, alkaline film-forming agent for high-carbon steel drawing of this invention is as follows: Phase 1: Tank Solution Preparation and Complexation Steady State (Core of Slag Prevention) During preparation, the strong chelating groups of sodium gluconate and potassium sodium tartrate preferentially bind to free Ca²⁺ in soluble calcium salts. +These compounds combine to form stable, water-soluble complexes. This significantly reduces the effective concentration of free calcium ions in the bath solution, thermodynamically inhibiting the rapid aggregation and precipitation of calcium stearate in the bath, achieving a "slag-free bath solution." Simultaneously, the complexation effect slows down the crystallization rate of calcium soap, and sodium gluconate and potassium sodium tartrate can also chelate residual ferrous ions on the surface of the wire brought into the alkaline bath solution after pickling, preventing the formation of sludge.

[0046] Phase Two: Dip Coating and In-situ Controlled Crystallization (Physical Adhesion) High-carbon steel wire is immersed in or sprayed with the alkaline coating agent. As the water drains, the complexation balance in the microenvironment of the metal surface is broken, and calcium ions are slowly released. These ions react in situ with modified fatty acid soaps to generate nano-sized, highly uniform calcium stearate crystals, making the coating surface smooth and dense with strong physical and mechanical adhesion.

[0047] Phase 3: Construction of hydrophobic network and micropore sealing (anti-moisture core) During the drying process, hydrophobically modified nano-silica is precisely embedded in the hydrophilic pores between calcium soap microcrystals, cutting off the capillary channels for water penetration. Meanwhile, the amino silicone oil emulsion is directionally spread on the film surface, with its siloxane backbone and amino side chains forming hydrogen bonds / van der Waals anchors with the polar groups on the calcium soap surface. Long-chain alkyl / polyether segments are arranged outwards, forming a flexible, low-surface-energy "lotus effect" hydrophobic network. The film surface contact angle is >105°, completely blocking water adsorption under high humidity conditions.

[0048] Phase Four: Anti-coking Synergy under Pulling Conditions (Operating Condition Assurance) Because the film surface is dry and has an extremely low coefficient of friction, the drawing powder remains dry and powdery during drawing, preventing hydrolysis, softening, or high-temperature carbonization. Uniform lubrication and the absence of localized hot spots fundamentally eliminate die scorching, die breakage, and wire skipping, significantly reducing die wear.

[0049] The potassium isostearate used in the following examples and comparative examples was prepared by neutralizing isostearic acid with potassium hydroxide. The isostearic acid (CAS30399-84-9) had an iodine value of ≤8 mgI2 / 100g and an acid value of 182±3 mgKOH / g.

[0050] The calcium gluconate used in the following examples and comparative examples is calcium gluconate monohydrate.

[0051] The hydrophobically modified nano silica used in the following examples and comparative examples is AEROSIL® R 972: nano silica that has been hydrophobically modified with dimethyldichlorosilane (DDS).

[0052] The amino silicone oil emulsion used in the following examples and comparative examples is CAS63148-62-0.

[0053] Example 1 A phosphorus-free, slag-free, moisture-absorbing, alkaline film-forming agent for drawing high-carbon steel comprises, by mass percentage: 15% modified fatty acid soap, 3% triethanolamine, 5% sodium gluconate, 2% potassium sodium tartrate, 5% hydrophobically modified nano-silica, 8% amino silicone oil emulsion, 5% calcium gluconate, with the balance being deionized water, and the pH adjusted to 9.8; the modified fatty acid soap comprises a mixture of potassium stearate and potassium isostearate in a mass ratio of 3:1.

[0054] The preparation method of the above-mentioned film-forming agent includes the following steps: (1) Heat the deionized water to 60°C, maintain the temperature, and add the ingredients sequentially while stirring; (2) Add 15% potassium stearate and potassium isostearate mixture (3:1) and 3% triethanolamine in sequence, and stir until completely transparent to obtain soap solution A; (3) Add 5% sodium gluconate and 2% potassium sodium tartrate to soap solution A, stir to dissolve, and obtain complex solution B; (4) 5% hydrophobically modified nano silica and 8% amino silicone oil emulsion (solid content 30%) were pre-dispersed and slowly added to complexing solution B and stirred for 40 minutes to obtain mixture C; (5) Dissolve 5% calcium gluconate in deionized water to obtain a 30wt% calcium gluconate solution. Slowly add the solution to mixture C, stir for 15 minutes until homogeneous, cool to room temperature, adjust the pH to 9.8, stop stirring, and filter through a 300-mesh filter.

[0055] Example 2 A phosphorus-free, slag-free, moisture-absorbing, alkaline film-forming agent for drawing high-carbon steel comprises, by mass percentage: 10% modified fatty acid soap, 2% triethanolamine, 3% sodium gluconate, 1.25% potassium sodium tartrate, 3% hydrophobically modified nano-silica, 5% amino silicone oil emulsion, 3% calcium gluconate, with the balance being deionized water, and the pH adjusted to 9.5; the modified fatty acid soap comprises a mixture of potassium stearate and potassium isostearate in a mass ratio of 3:1.

[0056] The preparation method is the same as in Example 1.

[0057] Example 3 A phosphorus-free, slag-free, moisture-absorbing alkaline coating agent for drawing high-carbon steel comprises, by mass percentage: 5% modified fatty acid soap, 1% triethanolamine, 1% sodium gluconate, 0.5% potassium sodium tartrate, 1% hydrophobically modified nano silica, 2% amino silicone oil emulsion, 1% calcium gluconate, with the balance being deionized water, and the pH adjusted to 9.2; the modified fatty acid soap comprises a mixture of potassium stearate and potassium isostearate in a mass ratio of 3:1.

[0058] The preparation method is the same as in Example 1.

[0059] Example 4 A phosphorus-free, slag-free, moisture-absorbing, alkaline coating agent for drawing high-carbon steel comprises, by mass percentage: 10% modified fatty acid soap, 2% triethanolamine, 5.92% sodium gluconate (Note: original 3% + 2.61% gluconate to compensate for calcium gluconate deficiency), 1.25% potassium sodium tartrate, 3% hydrophobically modified nano silica, 5% amino silicone oil emulsion, 0.74% anhydrous calcium chloride (Note: equivalent calcium ion to replace the original 3% calcium gluconate), with the balance being deionized water, and the pH adjusted to 9.5; the modified fatty acid soap comprises a mixture of potassium stearate and potassium isostearate in a mass ratio of 3:1.

[0060] The preparation method is the same as in Example 1.

[0061] Comparative Example 1 A film-forming agent comprising, by mass percentage: 10% modified fatty acid soap, 2% triethanolamine, 0.74% anhydrous calcium chloride, with the balance being deionized water, and pH adjusted to 9.5; the modified fatty acid soap comprising a mixture of potassium stearate and potassium isostearate in a mass ratio of 3:1.

[0062] The preparation method is the same as in Example 1.

[0063] This comparative example removes all the components of "sodium gluconate, potassium sodium tartrate, hydrophobically modified nano-silica, and amino silicone oil emulsion" from Example 2. Simultaneously, the soluble calcium salt "calcium gluconate" is replaced with an equivalent amount of "anhydrous calcium chloride," retaining only modified fatty acid soap + anhydrous calcium chloride + triethanolamine, with corresponding deionized water added. The replacement of calcium gluconate with calcium chloride eliminates the complexation interference from the gluconate ions inherent in the original calcium gluconate. This comparative example aims to simulate a traditional non-complexing agent system and verify the problems of loose film layer, easy moisture absorption, and slag formation in the bath caused by the "rapid adsorption and film formation of metal soap particles."

[0064] Comparative Example 2 A film-forming agent, by mass percentage, comprises: 10% modified fatty acid soap, 2% triethanolamine, 3% sodium gluconate, 1.25% potassium sodium tartrate, 3% ordinary hydrophilic nano silica, 5% amino silicone oil emulsion, 3% calcium gluconate, and the balance being deionized water, with pH adjusted to 9.5; the modified fatty acid soap comprises a mixture of potassium stearate and potassium isostearate in a mass ratio of 3:1, and the ordinary hydrophilic nano silica is CAS112945-52-5.

[0065] The preparation method is the same as in Example 1.

[0066] In this comparative example, the "hydrophobic modified nano silica" in Example 2 was replaced with an equal mass of "ordinary hydrophilic fumed silica".

[0067] Comparative Example 3 A film-forming agent, by mass percentage, comprises: 10% modified fatty acid soap, 2% triethanolamine, 3% hydrophobically modified nano silica, 5% amino silicone oil emulsion, 0.74% anhydrous calcium chloride, and the balance being deionized water, with pH adjusted to 9.5; the modified fatty acid soap comprises a mixture of potassium stearate and potassium isostearate in a mass ratio of 3:1.

[0068] The preparation method is the same as in Example 1.

[0069] In this comparative example, the "sodium gluconate and potassium sodium tartrate" in Example 2 were removed, and the soluble calcium salt "calcium gluconate" was replaced with "anhydrous calcium chloride" of equal calcium ion equivalent, and corresponding deionized water was added. The use of calcium chloride without complexing anions truly reflects the problem that when no external complexing agent is added, the bath solution is very likely to produce a large amount of sludge when it encounters ferrous ions brought in by acid washing.

[0070] Comparative Example 4 A film-forming agent, by mass percentage, comprises: 10% modified fatty acid soap, 2% triethanolamine, 3% sodium gluconate, 1.25% potassium sodium tartrate, 3% hydrophobically modified nano silica, 3% calcium gluconate, with the balance being deionized water, and the pH adjusted to 9.5; the modified fatty acid soap comprises a mixture of potassium stearate and potassium isostearate in a mass ratio of 3:1.

[0071] The preparation method is the same as in Example 1.

[0072] In this comparative example, the "amino silicone oil emulsion" in Example 2 was removed and replaced with an equal amount of deionized water to verify the effect of the absence of flexible silicone oil on the brittleness of the film and its resistance to wire skipping.

[0073] Comparative Example 5 A film-forming agent comprising, by mass percentage: 10% potassium stearate, 2% triethanolamine, 3% sodium gluconate, 1.25% potassium sodium tartrate, 3% hydrophobically modified nano silica, 5% amino silicone oil emulsion, 3% calcium gluconate, with the balance being deionized water, and the pH adjusted to 9.5.

[0074] The preparation method is the same as in Example 1.

[0075] In this comparative example, the "modified fatty acid soap (a mixture of potassium stearate and potassium isostearate)" in Example 2 was replaced with an equal mass of "potassium stearate alone". This verified that the calcium soap crystals formed by potassium stearate alone are too regular and are prone to hydrophilic micropores; while the branched structure of potassium isostearate can break the regular crystals, and the combination makes the film layer denser.

[0076] Comparative Example 6 A film-forming agent, by mass percentage, comprises: 10% modified fatty acid soap, 2% triethanolamine, 3% sodium gluconate, 1.25% potassium sodium tartrate, 3% hydrophobically modified nano-silica, 5% ordinary methyl silicone oil emulsion (amino-free), 3% calcium gluconate, and the balance being deionized water, with pH adjusted to 9.5; the modified fatty acid soap comprises a mixture of potassium stearate and potassium isostearate in a mass ratio of 3:1, and the ordinary methyl silicone oil emulsion (amino-free) has a viscosity of 1000-5000 mPa·s and an emulsion solid content of 30%.

[0077] The preparation method is the same as in Example 1.

[0078] In this comparative example, the "amino silicone oil emulsion" in Example 2 was replaced with an equal mass of "ordinary methyl silicone oil emulsion (without amino)" to verify the necessity of the "amino" in the silicone oil forming hydrogen bonds with the polar groups on the surface of the calcium soap. Ordinary silicone oil without amino has poor adhesion, and the hydrophobic network is prone to falling off and failing under pulling friction or high humidity conditions.

[0079] Comparative Example 7 A film-forming agent comprising, by weight percentage: 10% potassium isostearate, 2% triethanolamine, 3% sodium gluconate, 1.25% potassium sodium tartrate, 3% hydrophobically modified nano silica, 5% amino silicone oil emulsion, 3% calcium gluconate, with the balance being deionized water, and the pH adjusted to 9.5.

[0080] The preparation method is the same as in Example 1.

[0081] In this comparative example, the "modified fatty acid soap (a mixture of potassium stearate and potassium isostearate, in a mass ratio of 3:1)" in Example 2 was replaced with an equal mass of "monoisostearate".

[0082] Comparative Example 8 A film-forming agent, by mass percentage, comprises: 10% modified fatty acid soap, 2% triethanolamine, 4.25% sodium gluconate, 3% hydrophobically modified nano silica, 5% amino silicone oil emulsion, 3% calcium gluconate, with the balance being deionized water, and the pH adjusted to 9.5; the modified fatty acid soap comprises a mixture of potassium stearate and potassium isostearate in a mass ratio of 3:1.

[0083] The preparation method is the same as in Example 1.

[0084] In this comparative example, "1.25% potassium sodium tartrate" was removed from Example 2, and sodium gluconate was increased from 3% to 4.25%, while keeping the total complexing agent content unchanged.

[0085] Comparative Example 9 A film-forming agent, by mass percentage, comprises: 10% modified fatty acid soap, 2% triethanolamine, 7.17% sodium potassium tartrate, 3% hydrophobically modified nano-silica, 5% amino silicone oil emulsion, 0.74% anhydrous calcium chloride (note: equivalent calcium ions replace the original 3% calcium gluconate), with the balance being deionized water, and the pH adjusted to 9.5; the modified fatty acid soap comprises a mixture of potassium stearate and potassium isostearate in a mass ratio of 3:1.

[0086] The preparation method is the same as in Example 1.

[0087] In this comparative example, the soluble calcium salt "calcium gluconate" in Example 2 was replaced with "anhydrous calcium chloride" of equal calcium ion equivalent, while "sodium gluconate 3%" was removed and the potassium sodium tartrate content was increased from 1.25% to 7.17%, while keeping the total complexing agent content unchanged.

[0088] Performance testing 1. Immerse Φ5.5mm high carbon steel wire in the film-forming agents of Examples 1-4 and Comparative Examples 1-9 for 240 seconds, drain, coat with wire drawing powder, draw and shape, and test.

[0089] 1. Moisture Absorption Resistance Test: Place the treated wire in a constant temperature and humidity chamber (40℃, 90%RH) for 24 hours. After removal, weigh the wire and calculate the water absorption rate. Observe the color change using cobalt chloride test paper applied to the surface (pink indicates moisture absorption, blue indicates dryness). Judgment criteria: If the test paper remains blue or only turns very light purple, it is judged as "no free water / moisture absorption resistance qualified"; if the test paper turns obvious pink, it is judged as "free water present on the surface / moisture absorption resistance unqualified".

[0090] Water absorption rate = (weight after high humidity - initial weight) / initial weight × 100%; on-site qualitative analysis using cobalt chloride test paper color change method.

[0091] 2. Tank solution sediment (tank solution stability) test: After the tank solution is introduced into the acid solution, it is allowed to stand for 24 hours, and the height of the bottom sediment is measured; specifically, the graduated cylinder standing method is used: take 50 mL of tank solution, add 10 mL of 20% concentration hydrochloric acid, and read the volume / height of the bottom sediment layer.

[0092] 3. Drawing Coking and Working Condition Test: On a small wire drawing machine in the laboratory, 500 meters of Φ5.5mm high carbon steel wire were drawn at the actual production speed. If a wire skipping occurred in the middle, the machine was stopped in advance. After stopping the machine, the working cone surface of the mold was observed with a metallographic microscope and rated according to the coking area (0 grade: no coking; 5 grade: severe coking, mold prying is required).

[0093] The test results are shown in Table 1 below: Table 1:

[0094] 2. The high-carbon steel test pieces were immersed in the alkaline film-forming agents of Examples 1-4 and Comparative Examples 1-9 for 240 seconds, dried (70~80℃, 5min) and then tested.

[0095] 1. Membrane weight test: Take a known surface area (S, m²) 2 The high-carbon steel test piece with an initial weight (W1, g) was treated with this film-forming agent and dried under specified conditions (e.g., dried at 105°C to constant weight), and its weight (W2, g) was measured.

[0096] Membrane weight (g / m 2 ) = (W2-W1) / S.

[0097] 2. Uniformity evaluation: Five samples are randomly selected from each group for testing. The mean and standard deviation are calculated. The smaller the standard deviation, the better the uniformity of the in-situ controlled crystallization film formation.

[0098] 3. Observe the macroscopic appearance of the film and perform a cross-cut test.

[0099] The test results are shown in Table 2 below: Table 2:

[0100] High-carbon steel specimens from Examples 2 and 5, after being impregnated with an alkaline coating agent and dried, were tested using electron microscopy and energy dispersive spectroscopy. The electron microscopy results are as follows: Figure 1 The energy spectrum is shown in Table 3 below.

[0101] Table 3:

[0102] As can be seen from SEM, the film layer of Example 2 is finer and denser than that of Comparative Example 5. EDS results also show that the film layer of Comparative Example 5 is loose and the iron content measured on the surface of the wire is higher, while the film layer of Example 2 is dense and has less exposed iron substrate.

[0103] The above is a detailed description of the preferred embodiments of the present invention. However, the present invention is not limited to the embodiments described. Those skilled in the art can make various equivalent modifications or substitutions without departing from the spirit of the present invention. All such equivalent modifications or substitutions are included within the scope defined by the claims of the present invention.

Claims

1. A phosphorus-free, slag-free, moisture-absorbing, alkaline film-forming agent for drawing high-carbon steel, characterized in that, By mass percentage, it includes the following components: Modified fatty acid soap 5%~15%; Soluble calcium salts 1%~5%; 1%~5% hydrophobically modified nano-silica; Amino silicone oil emulsion 2%~8%; Gluconate 1%~5%; Tartrates 0.5%~2%; Triethanolamine 1%~3%; Deionized water balance; Modified fatty acid soaps include stearate and isostearate, with a mass ratio of stearate to isostearate of 3:1 to 5:

1.

2. The phosphorus-free, slag-free, moisture-absorbing, alkaline film-forming agent for high-carbon steel drawing according to claim 1, characterized in that, Stearates are potassium stearate and / or sodium stearate; Isostearates are potassium isostearate and / or sodium isostearate; Soluble calcium salts are one or more of calcium gluconate, calcium chloride, and calcium nitrate.

3. The phosphorus-free, slag-free, moisture-absorbing alkaline film-forming agent for high-carbon steel drawing according to claim 1, characterized in that, The mass ratio of gluconate to calcium ions in alkaline film-forming agents is 5:1 to 20:

1.

4. The phosphorus-free, slag-free, moisture-absorbing, alkaline film-forming agent for high-carbon steel drawing according to claim 1, characterized in that, The hydrophobically modified nano-silica is fumed silica with a water contact angle ≥110° after surface modification with long-chain alkylsilanes. Amino silicone oil emulsions are amino-terminated or side-amino-modified silicone oil emulsions with a solid content of 20% to 40%. Gluconate is sodium gluconate and / or potassium gluconate; Tartrate is potassium sodium tartrate.

5. The phosphorus-free, slag-free, moisture-absorbing, alkaline film-forming agent for high-carbon steel drawing according to claim 1, characterized in that, The pH of alkaline film-forming agents is 9.0~10.

5.

6. The method for preparing the phosphorus-free, slag-free, moisture-absorbing, alkaline film agent for high-carbon steel drawing according to any one of claims 1-5, characterized in that, Includes the following steps: Under stirring conditions, modified fatty acid soap and triethanolamine are added to heated deionized water, followed by gluconate and tartrate, then hydrophobically modified nano-silica and amino silicone oil emulsion, and finally soluble calcium salt. After cooling, the pH is adjusted to obtain a phosphorus-free, slag-free, moisture-absorbing alkaline coating agent for high carbon steel drawing.

7. The method for preparing the phosphorus-free, slag-free, moisture-absorbing, alkaline film agent for high-carbon steel drawing according to claim 6, characterized in that, The temperature of the heated deionized water is 50~60℃; After adding the modified fatty acid soap and triethanolamine, stir until completely dissolved; After adding gluconate and tartrate, stir until completely dissolved; After adding the hydrophobically modified nano-silica and amino silicone oil emulsion, stir for 30-45 minutes; Hydrophobically modified nano-silica and amino silicone oil emulsion are premixed evenly; After adding the soluble calcium salt, stir for 15-30 minutes; Soluble calcium salts are pre-dissolved in deionized water at a concentration of 30-50% by mass. After adjusting the pH, filter through a 200-400 mesh screen.

8. The application of the phosphorus-free, slag-free, moisture-absorbing, alkaline film-forming agent for high-carbon steel drawing according to any one of claims 1-5 or the preparation method according to any one of claims 6-7 in the drawing of high-carbon steel.

9. A method for drawing high-carbon steel, characterized in that, Includes the following steps: High-carbon steel is immersed or sprayed with the phosphorus-free, slag-free, moisture-absorbing, alkaline film agent for high-carbon steel drawing according to any one of claims 1-5 or the preparation method according to any one of claims 6-7, drained or dried, and then coated with drawing powder for drawing.

10. The high-carbon steel drawing method according to claim 9, characterized in that, High-carbon steel is pre-degreased, derusted, and washed with water until neutral. High-carbon steel is used for wire rods; The immersion time of high carbon steel in alkaline coating agent is 240~300 seconds; The drying temperature is 70~80℃, and the time is 240~300 seconds.